THE IDENTITY (IES) OF THE WOMAN TRANSLATED IN CONCEPTS DENOMINATED BY THE TERM CASAMENTO CIVIL THROUGH OUT THE HISTORY OF BRAZILIAN LEGISLATION - Curti-Contessoto, Beatriz; Deângeli, Maria Angélica [UNESP]; Barros, Lidia Almeida [UNESP] (GN1 Sistemas e Publicacoes, 2021)
This paper intends to discuss how the concepts denominated by the term casamento civil translate the identity (ies) of woman from its institution in 1890 to 2002, when the last change on the rights of women occurred in the context of Brazilian marriages. To do so, we are based on studies on cultural identity in postmodernity (Silva et al. 2012; Hall 2001; among others), relating them to the forms of symbolic domination (Bourdieu 2016), to feminism (Miguel and Biroli 2014) and to the issue of language in the feminist perspective (Figueiredo 2013). Thus, we observe that the conceptual evolution of the term casamento civil has translated different identities of women over the years (from submissive to husband to equal to man) in the specific context of Brazilian Civil Law. Despite this change, we conclude that there are other forms of domination, which are the result of machismo and patriarchy that have sustained (and still sustain) relations in our society.
LA(S) IDENTIDAD(ES) DE LA MUJER TRADUCIDA(S) EN LOS CONCEPTOS DENOMINADOS CON EL TÉRMINO CASAMENTO CIVIL EN LA HISTORIA DE LA LEGISLACIÓN BRASILEÑA
A(S) IDENTIDADE(S) DA MULHER TRADUZIDA(S) NOS CONCEITOS DENOMINADOS PELO TERMO CASAMENTO CIVIL AO LONGO DA HISTÓRIA DA LEGISLAÇÃO BRASILEIRA
Keywords: Civil marriage; Feminism; Identity; Language; Woman